Intrahepatic Cholestasis Of Pregnancy - A Review - Ome Kulsoom; Shahina Ishtiaq; Rubina Hussain (ziauddin University, 2018)
Intrahepatic cholestasis of pregnancy (ICP) is a complex disease described by pruritus connected with elevated serum bile acid or amino transferase level. Usually,it occurs to the third trimester of pregnancy and improves itself after delivery.In 1970's the prevalence was reported highest in Bolivia and Chile, however, the prevalence in United States (US) ranges in between 0.3 to 5.6%, whereas, in Europe it is 0.5 to 1.5%. The awareness campaigns of the disease showed an increase in incidence in the high-incidence regions because of more reporting of the cases.Ursodeoxycholicacid (dose) is the treatment of choice for ICP. This treatment provide improved liver function and relief in pruritus and is considered safe during pregnancy.At the molecular level, it offers cytoprotection against hepatotoxic effects of hydrophobic bile acids, improves hepatobiliary bile acid transport, and decreases plasma bile acids. Moreover, to alleviate the pruritus; hydroxyzine or an aqueous cream with 1% methanol were used.ICP is a unique hepatic disorder in pregnancy with possibly an interaction of genetic, hormonal, and environmental factors in its etiopathogenesis, although the definite etiology still remains obscure.